Development of a Novel Cervical Deformity Surgical Invasiveness Index. Issue 2 (15th January 2020) - Passias, Peter G.; Horn, Samantha R.; Soroceanu, Alexandra; Oh, Cheongeun; Ailon, Tamir; Neuman, Brian J.; Lafage, Virginie; Lafage, Renaud; Smith, Justin S.; Line, Breton; Bortz, Cole A.; Segreto, Frank A.; et al.
Abstract : Study Design: Retrospective review. Objective: The aim of this study was to develop a novel surgical invasiveness index for cervical deformity (CD) surgery that incorporates CD-specific parameters. Summary of Background Data: There has been a surgical invasiveness index for general spine surgery and adult spinal deformity, but a CD index has not been developed. Methods: CD was defined as at least one of the following: C2-C7 Cobb >10°, cervical lordosis (CL) >10°, cervical sagittal vertical axis (cSVA) >4 cm, chin brow vertical angle >25°. Consensus from experienced spine and neurosurgeons selected weightings for each variable that went into the invasiveness index. Binary logistic regression predicted high operative time (>338 minutes), estimated blood loss (EBL) (>600 mL), or length of stay (LOS) >5 days) based on the median values of operative time, EBL, and LOS. Multivariable regression modeling was utilized to construct a final model incorporating the strongest combination of factors to predict operative time, LOS, and EBL. Results: Eighty-five CD patients were included (61 years, 66% females). The variables in the newly developed CD invasiveness index with their corresponding weightings were: history of previous cervical surgery (3), anterior cervical discectomy and fusion (2/level), corpectomy (4/level), levels fused (1/level), implants (1/level), posterior decompression (2/level), Smith-Peterson osteotomy (2/level), three-column osteotomy (8/level), fusion to upper cervical spine (2), absolute change in T1 slope minus cervical lordosis, cSVA, T4-T12 thoracic kyphosis (TK), and sagittal vertical axis (SVA) from baseline to 1-year. The newly developed CD-specific invasiveness index strongly predicted long LOS ( R 2 = 0.310, P < 0.001), high EBL ( R 2 = 0.170, P = 0.011), and extended operative time ( R 2 = 0.207, P = 0.031). A second analysis used multivariable regression modeling to determine which combination of factors in the newly developed index were the strongest determinants of operative time, LOS, and EBL. The final predictive model included: number of corpectomies, levels fused, decompression, combined approach, and absolute changes in SVA, cSVA, and TK. This model predicted EBL ( R 2 = 0.26), operative time ( R 2 = 0.12), and LOS ( R 2 = 0.13). Conclusion: Extended LOS, operative time, and high blood loss were strongly predicted by the newly developed CD invasiveness index, incorporating surgical factors and radiographic parameters clinically relevant for patients undergoing CD corrective surgery. Level of Evidence: 4 Abstract : An invasiveness index has yet to be developed specifically for cervical deformity (CD) surgery. Extended length of stay, operative time, and high blood loss were strongly predicted by the newly developed CD invasiveness index, incorporating surgical factors and radiographic parameters clinically relevant for patients undergoing CD corrective surgery.